Negative impact of COVID-19 home confinement on physical performance of elite youth basketball players - Salazar, H.; Svilar, L.; Garcia, L.; González-Lago, L.; Castellano, J. (Sport Performance & Science Reports, 2020)
Early in 2020 the world witnessed the global outbreak of new virus named coronavirus disease or COVID-19. Sport activities of any kind were abruptly stopped and players, coaches and other personnel were obliged to home con nement together with general population. In Spain, mandatory quarantine was announced on March 14th and players were able to return to train with coaching supervision on May 14th after conducting o cial medical inspection. During the period of 60 days players were forced to train at home with poor resources of equipment, without adequate communication with coaches, as well as minimal sunlight exposure due to forbidden outdoor activities. In the quarantine, many players did not train much, some focused on bodyweight strength while others used stationary bikes for conditioning. Regardless of training type, it was obvious that basketball players will face detraining, a phenomenon de ned as decrement in physical performance due to cessation of training activities. As jumping, sprinting and change of direction activities were minimized or completely ceased, loss of performance for basketball players was immense. Firstly, signi cant decrements in power qualities come a result of changes in muscle size and architecture, as well as tendon properties what further leads to reduction in muscle strength, power and rate of force development. Secondly, drop in cardiorespiratory function lead to impaired aerobic capacity and anaerobic endurance of players. Thirdly, players were also challenged to change and adjust their nutritional habits in order to minimize muscle atrophy and avoid excessive gains of body fat.